Efetividade dos aparelhos intrabucais de avanço mandibular no tratamento do ronco e da síndrome da apneia e hipopneia obstrutiva do sono (SAHOS): Revisão sistemática - Caldas, Sergei Godeiro Fernandes Rabelo [UNESP]; Ribeiro, Alexandre Antonio; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Martins, Lidia Parsekian [UNESP]; Matoso, Rildo Medeiros (FapUNIFESP (SciELO), 2009)
Introduction: The snoring is produced by the vibration of the soft palatum and/or other oropharyngeal tissues, during the air passage, in the breathing function. OSAHS is defined as the closing of 30%, at least, of the nasal/ buccal airway for 10 seconds or more, in spite of existing inspiratory effort, accompanied by oxyhemoglobin de- saturation of 4% or more. Objectives: To evaluate the available scientific evidence about the use of mandibular advancement intraoral appliances in the treatment of the snoring and/or OSAHS. Methodology: Electronic search strategy using predefined key-words and criteria was realized including studies published until October of 2008. It was also used the qualitative evaluation of the articles methodology. Results: Although a significant number of articles has studied this subject, only 7 articles showed methodological quality to be included in this systematic review. Conclusions: The intraoral appliances are widely prescribed for the treatment of snoring and OSAHS as primary therapy and as an alternative to patients who are unable to tolerate the positive airway pressure therapy.
The effectiveness of mandibular advancement intraoral appliances in the treatment of the snoring and obstructive sleep apnea and hypopnea syndrome (OSAHS): Systematic review
Keywords: Mandibular advancement; Obstructive sleep apnea; Orthodontic appliances; Sleep disorders